Design Pitot Tube Cover with Artificial Intelligence (Arduino) Based Warning System on Piper Seneca V Aircraft - Dimas Endrawan Putra; Untung Lestari Nur Wibowo; Wisnu Kuncoro; Muhamad Khoirul Anam (Jurnal Penelitian Pendidikan IPA, 2023)
The pitot tube is a component in the fuselage to measure the pressure generated by air movement or wind, while the placement of the pitot tube is usually on the wing. A trivial thing that can be fatal is that before flying, sometimes the pilot/flight instructor neglects to remove the pitot tank cover. This negligence resulted in the malfunctioning of the Air Speed Indicator (ASI), Vertical Speed Indicator and Altimeter. Appropriate technology in the form of a pitot tube cover with a warning using an ultrasonic sensor with the support of artificial intelligence technology using Arduino has been applied to the Piper Seneca V aircraft to prevent negligence in removing the pitot tube cover before flying. The Piper Seneca V has been chosen as the object of the application of technology because the Piper Seneca V type aircraft is of the low wing type so that the pitot tubes are not visible when not inspecting the underside of the aircraft's wings. During 30 days of testing with 12 hours of testing time each day and exposure to different temperatures and humidity each day, both battery life and component resistance can be ensured that they are still in optimal conditions. During testing in the simulation room, the tool worked well with a 1 meter object detection configuration. Using a 3.7 volt battery with a storage capacity of 1600 mAh can make the device last for 4 days with 2 hours of recharging time.